Performance : a critical introduction - Carlson, Marvin, 1935- (Milton Park, Abingdon, Oxon ; New York : Routledge, 2017)
This book provides an overview of the modern concept of performance and how it has developed in various fields. Topics discussed include the evolution of performance art since the 1960s and performance in society
P.B
Includes bibliographical references.
Keywords: Arts, American -- 20th century; Arts, Modern -- 20th century; Performance art -- United States; Performance art